Hamka’s Sufism in The Literary Work “Tenggelamnya Kapal Van Der Wijck” on Schleiermacher’s Hermeneutics Perspective - AR. Miftah Al Farouqy; Helmi Syaifuddin; Ahmad Barizi (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2024)
Hamka was a prolific poet scholar who brought the idea of reforming Sufism, known as neo-Sufism. As a poet, he wrote many literary works, such as “Tenggelamnya Kapal Van der Wijck” which was written at the same time as modern Sufism, also contains elements of Sufism. This research aims to (1) identify Hamka's sufistic texts in “The Sinking of van Der Wijck”, (2) analyze the sufistic meaning in it’s work on Schleiermacher's hermeneutic perspective. “Tenggelamnya Kapal Van der Wijck” is one of Hamka's literary works that is considered to contain sufistic values. The authors analyzed the sufistic texts in Schleirmacher’s hermeneutics perspective, a relevant approach to derive the meaning of Hamka’s literary texts. This research is in the form of qualitative research and is categorized as library research with a text analysis method. Data is obtained through documentary techniques, and data sources are taken from books and secondary notes that are relevant to the research theme. The data is then analyzed using Schleiermacher's hermeneutic working principles by means of grammatical and psychological interpretations. The result of this study is (1) Hamka's Sufism in “Tenggelamnya Kapal Van der Wijck” found in the text of the story in the aspects of: natural beauty, a quest for true happiness, good manners, and love. (2) After going through interpretation and analysis stages using perspective of Schleirmacher’s hermeneutics, the meaning of these aspects of sufistic text is love, which is natural giving (fiṭrah), and must be maintained by declaring self to Allah, natural beauty as an introduction to reaching maqām riḍā, good manners as a means of knowing Allah, and true happiness is ma'rifatullāh